Occurrence, distribution, and health risk assessment of quinolone antibiotics in water, sediment, and fish species of Qingshitan reservoir, South China - Huang, Liangliang; Mo, Yuanmin; Wu, Zhiqiang; Rad, Saeed; Song, Xiaohong; Zeng, Honghu; Bashir, Safdar; Kang, Bin; Chen, Zhongbing (Scientific reports, 2020)
The residual antibiotics in the environment have lately caused widespread concerns. However, little information is available on the antibiotic bioaccumulation and its health risk in drinking water resources of South China. Therefore, the occurrence, distribution, and health risk of four quinolone antibiotics including ofloxacin (OFX), norfloxacin (NOR), ciprofloxacin (CIP), and enrofloxacin (ENR) in the Qingshitan reservoir using high-performance liquid chromatography were investigated. Results revealed that the concentrations in water, sediment, and edible fish ranged from 3.49-660.13 ng/L, 1.03-722.18 μg/kg, and 6.73-968.66 μg/kg, respectively. The ecological risk assessment via the risk quotient (RQ) method showed that the values in sediment were all greater than 1, posing a high risk to the environment. The health risk index of water samples was at the maximum acceptable level, with OFX at the top while the rest were at the medium risk level. The main edible fish kinds of the reservoir had high dietary safety and the highest contaminations were found in carnivorous feeding habits and demersal habitat fishes with OFX as the highest magnitude. Source identification and correlation analysis using SPSS showed significant relationships between NOR with pH and turbidity (in water), as well as total phosphor (TP) and total organic carbon (TOC) in sediment. NOR was the highest in sediment which mostly sourced from livestock wastewater, croplands irrigation drain water, and stormwater. Correlations between CIP and ENR with TP were significant, while OFX was positively associated with total nitrogen (TN) which mainly originated from urban sewage as well as directly dosed drugs in fish farms. In conclusion, our results are of great significance for ensuring the safety of drinking water and aquatic products in this region.
Keywords: Čína; monitorování životního prostředí; řízení kvality; Anti-Bacterial Agents; Quinolones; Risk Assessment; Environmental Monitoring; Quality Control; China; Geologic Sediments; řeky; Rivers; chemické látky znečišťující vodu; geologické sedimenty; chinolony; Water Pollutants, Chemical; hodnocení rizik; zvířata; antibakteriální látky; Fishes; ryby; Animals